Factors Influencing Job Satisfaction of New Graduate Nurses Participating in Nurse Residency Programs: A Systematic Review - Lin, Patrice S.; Viscardi, Molly Kreider; McHugh, Matthew D. (The Journal of continuing education in nursing, 2014)
Nurse residency programs are designed to increase competence and skill, and ease the transition from student to new graduate nurse. These programs also offer the possibility to positively influence the job satisfaction of new graduate nurses, which could decrease poor nursing outcomes. However, little is known about the impact of participation in a nurse residency program on new graduate nurses' satisfaction. This review examines factors that influence job satisfaction of nurse residency program participants. Eleven studies were selected for inclusion, and seven domains influencing new graduate nurses' satisfaction during participation in nurse residency programs were identified: extrinsic rewards, scheduling, interactions and support, praise and recognition, professional opportunities, work environment, and hospital system. Within these domains, the evidence for improved satisfaction with nurse residency program participation was mixed. Further research is necessary to understand how nurse residency programs can be designed to improve satisfaction and increase positive nurse outcomes.